An introduction to bioenergy and landscape restoration - Baral, H.; Leksono, B.; Seol, M. (Center for International Forestry Research, 2022)
Land degradation is becoming a global challenge, with Indonesia being no exception. Rising populations and their associated food and biomaterial demands have accelerated the conversion of forests for other land uses; a trend that persists in many parts of the world. Forest landscape restoration (FLR) is being promoted as a means for reversing land degradation while providing multiple products and services, including bioenergy. FLR using biofuel-friendly trees under climate smart agroforestry practices and utilizing fruits, nuts and biomass for energy could solve multiple issues by turning unproductive degraded lands into productive landscapes; preventing further conversion of natural vegetation for other uses; compensating for the high initial investments required for FLR; and providing multiple ecosystem services, including climate regulation. The chapters in this book investigate multiple issues associated with FLR and bioenergy, such as policy analysis, geospatial assessment for identifying land suitability, farmers’ perceptions and species-specific details useful for land managers, planners and policymakers.